2017
DOI: 10.1111/obr.12511
|View full text |Cite
|
Sign up to set email alerts
|

What characteristics of nutrition and physical activity interventions are key to effectively reducing weight gain in obese or overweight pregnant women? A systematic review and meta‐analysis

Abstract: When PCPs counsel nutrition and physical activity, obese and overweight pregnant women have greater success meeting GWG targets and may be more motivated to modify their behaviour than with other modes of intervention deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 63 publications
(155 reference statements)
5
73
0
4
Order By: Relevance
“…In this review, we found that 21 randomized controlled trials of healthy eating and/or physical activity limited an average of 1.81 kg of gestational weight gain among pregnant overweight and obese women receiving the intervention as compared to those receiving no intervention. This finding is in concert with those (−1.71 to −2.21 kg) found in previous reviews on pregnant overweight and obese women . Healthy eating intervention in our review had a larger effect size than those of physical activity alone or combined intervention in limiting gestational weight gain.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this review, we found that 21 randomized controlled trials of healthy eating and/or physical activity limited an average of 1.81 kg of gestational weight gain among pregnant overweight and obese women receiving the intervention as compared to those receiving no intervention. This finding is in concert with those (−1.71 to −2.21 kg) found in previous reviews on pregnant overweight and obese women . Healthy eating intervention in our review had a larger effect size than those of physical activity alone or combined intervention in limiting gestational weight gain.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported in several systematic reviews that pregnant women who receive healthy eating and/or physical activity interventions have a risk reduction of excessive gestational weight gain of 20% or an average of 0.91–5.37 kg less gestational weight gain than women receiving no such interventions. Frameworks used to define healthy eating and physical activity, however, varied among review papers.…”
Section: Findings From Previous Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of lifestyle interventions aimed at managing weight gain during pregnancy, Yeo et al . reported significantly less gestational weight gain for interventions delivered by a prenatal care provider versus those delivered by nonclinicians (weighted mean difference −3.88 kg versus −0.80 kg; P = 0.005). Despite this result being derived from studies in pregnancy, it illustrates the importance of women receiving healthcare advice from qualified health practitioners to manage maternal weight.…”
Section: Introductionmentioning
confidence: 99%
“…35 The frequency and duration of interventions during pregnancy were not uniform, ranging from frequent contact every 1–2 weeks to minimal interaction over the course of the pregnancy. The implementation of the interventions varied including who provided the intervention (nutritionists, therapists, nurses, physicians) 36,37 and whether the intervention was in person or online 38,39 or provided as individual or group sessions. 29,40 Thus, the optimal intervention type is unknown.…”
mentioning
confidence: 99%